Effect of controlled cold air distribution on temperature profile and phase transformation of wire loops in the Stelmor air-cooling process. (October 2018) - Huang, Junkai; Wang, Bo; Xue, Fei; Liu, Shanshan; Hong, Lingxiang; Yu, Yaowei; Zhang, Jieyu
Highlights: 3-D mathematic model coupling air flow, heat transfer and phase transform was set up. 3-D physical model base on complex structure of wire loops was established. The dynamic temperature and phase transformation distribution was predicted. Applying type B nozzle can efficiently reduce the temperature inhomogeneity. Abstract: Wire rods produced by the Stelmor air cooling process were found to have the problem of microstructure non-uniformity. The proper distribution of cold air from the nozzle of the plenum chamber can adjust the convection heat transfer intensity at the different positions of wire loops, and further control the dynamic distribution of temperature and phase transformation on wire rods. A three-dimensional mathematical model incorporating the turbulent flow of air, heat transfer and the JMAK phase transform model in the Stelmor process has been developed. Two types of air nozzle were applied in our study, and Type B nozzle which blocked the center portion applied more air to the side region of wire loops than the Type A nozzle. Compared to the unblocked nozzle, the type B nozzle can effectively reduce the temperature difference between the low dense zone and high dense zone on the wire loops from 69.7 K to 18.4 K. The simulated temperature results of wire loop agreed well with the measured one in the industry trials. The present study has demonstrated that these models can be useful tool for optimizing cooling condition in the Stelmor process and predicting the temperature profile and microstructure evolution of the wire rods.